Penerapan Model Guided Discovery Learning untuk Mempertahankan Hasil Belajar Matematika Siswa Kelas VII Smp Negeri 1 Pandaan selama Pandemi Covid-19 Tahun Ajaran 2020/2021 - Tarsiyah, Tarsiyah (Jurnal Likhitaprajna, 2021)
This study aims to describe the learning outcomes of the seventh grade students of SMP Negeri 1 Pandaan in mathematics subject to one variable linear equation material during the Covid-19 pandemic in the academic year of 2020/2021 by applying the guided discovery learning model. This study type is Classroom Action Research by implementing 4 steps, namely: (1) Plan; (2) act); (3) observe, and (4) reflect. The research subjects were 34 grade VII J students of SMP Negeri 1 Pandaan. The data collection techniques were observation and test. The data analysis technique consists of two types, namely qualitative data analysis techniques and quantitative data analysis techniques. The results showed that the learning outcomes of students who completed the first cycle reached 79% (27 students) and 21% (7 students) had not completed the study, while in the second cycle it reached 88% (30 students) and only 12% had not completed ( 4 students).